Co-creating Safer Urban Spaces: Educational Impacts of Student Participation in the “Odasis” CPTED Project in Jakarta - Jeon, Jeong Ok; Rakhman, Rizki Taufik; Murwanti, Aprina; Pahala, Agam Akbar; Jung, Jae Hak (Harmonia: Journal of Arts Research and Education, 2025)
Community safety in rapidly growing cities like Jakarta is closely tied to the design of public spaces, as rising urban crime rates continue to challenge local environments. This study examines how Crime Prevention Through Environmental Design (CPTED) principles can be integrated into student-led public art learning activities. Specifically, it reviews the first, site-survey phase of ODASIS—a Korean arts and culture ODA initiative implemented in Jakarta in May 2025—focusing on the educational impacts of students’ participation. Using a Participatory Action Research (PAR) approach, the study investigates how collaborative field activities—such as problem identification, safety mapping, and idea generation—enhance learning and community awareness. The project involved twenty Indonesian visual art education students from Universitas Negeri Jakarta (UNJ) and four architecture students from Gwangju University, mentored by a professional architect from Seoul. The findings reveal that the CPTED site survey (1) deepened students’ understanding of community safety and public space design; (2) encouraged them to generate locally relevant solutions through dialogue with residents; (3) fostered cross-cultural and interdisciplinary collaboration; and (4) strengthened their civic and social responsibility. Academically, this study contributes to the discourse on experiential learning in public art education; practically, it demonstrates how CPTED-based art projects can function as educational tools for community engagement. The project’s broader social impact will be further examined in the forthcoming second phase in August 2025, which focuses on implementing design interventions.